Answer:
6x-3
Step-by-step explanation:
-1, -8
0, -9
1, -10
2, -11
Hope that helps!
4 times 3.14 times 8 squared
803.8
Answer:
14+5 = 19
19 + 15/2
15/2 = 7.5
19+7.5 = 26.5
Just remember PEMDAS!
Pls mark brainliest
Step-by-step explanation:
Answer:
(f + g)(3) = 9
Step-by-step explanation:
Given:
f(x) = x² + 1
g(x) = x - 4
Required:
(f + g)(3)
SOLUTION:
✔️Find f(3) by substituting x = 3 into f(x) = x² + 1:
f(3) = (3)² + 1 = 9 + 1
f(3) = 10
✔️Find g(3) by substituting x = 3 into g(x) = x - 4:
g(3) = 3 - 4
g(3) = -1
✔️Find (f + g)(3):
(f + g)(3) = f(3) + g(3)
= 10 + (-1)
= 10 - 1
(f + g)(3) = 9